Concise Review: Induced Pluripotent Stem Cells as New Model Systems in Oncology. (29th July 2015) - Laplane, Lucie; Beke, Allan; Vainchenker, William; Solary, Eric
Abstract : The demonstration that pluripotent stem cells could be generated by somatic cell reprogramming led to wonder if these so-called induced pluripotent stem (iPS) cells would extend our investigation capabilities in the cancer research field. The first iPS cells derived from cancer cells have now revealed the benefits and potential pitfalls of this new model. iPS cells appear to be an innovative approach to decipher the steps of cell transformation as well as to screen the activity and toxicity of anticancer drugs. A better understanding of the impact of reprogramming on cancer cell-specific features as well as improvements in culture conditions to integrate the role of the microenvironment in their behavior may strengthen the epistemic interest of iPS cells as model systems in oncology. Stem Cells   2015;33:2887–2892